Geographical information systems, tourism - Cruz, Cláudia (2014)
Geographical information systems (GIS) have been defined by different authors, some before the 1970s, when GIS started to expand. A common definition is “a powerful set of tools for storing and retrieving at will, transforming and displaying spatial data from the real world for a particular set of purposes” (Burrough 1986:6). In this way, GIS can be considered as a powerful tool for the management and decision-making process in tourism. GIS has the ability to represent, store, manage, analyze, update, and visualize spatial and regular data in an integrated environment. These tools operate on two data elements (Bahaire and Elliott-White 1999): geographical or spatial data (locational aspects) and attribute data (statistical and non-locational data associated with a spatial entity). As powerful tools, they combine a geographical analysis with an attribute analysis, providing a better interpretation of the data. Research fields (such as geography, urban development and planning, environmen ...